THE PSALMS, THE HYMNS, AND THE TEXTS OF THE OLD TESTAMENT AND THEIR USE IN HOLY MONDAY AND TUESDAY - ARTEMI, Eirini (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
The worship of the Orthodox Eastern Church involves a multitude of references hints and images of the Old Testament, in all the sequences (liturgies) and hymns. Particularly in the Holy and Great Week, the texts of the Old Testament are used with particular emphasis. On Holy Monday and on Holy Tuesday there is use of the texts of the Old Testament. Holy and Great Monday, Tuesday and Wednesday remind us of the eschatological meaning of Pascha. In this paper, we are going to analyze the real and deep influence of the Old Testament to these days of Holy Monday and Tuesday and why the Orthodox Church chose to use the Old Testament although the Jews refused Christ and led him to death. The goal is to show that Orthodox Greek Christians use these texts from the Old Testament because they have no hostile attitude against Jews.